The Concept of Sulūk in Yogyakarta’s Masangin Tradition: Reinterpreting the Symbolism of Spiritual Journey - Nashrul Mu'minin; Nuraini Rahmawati; Wathanan Srinin; Mowafg Abrahem Masuwd; Taufik Nughro (LaKaspia, 2026)
Objective: The Masangin tradition at Alun-Alun Kidul, Yogyakarta, has long been understood as a ritual in which blindfolded participants attempt to walk through the narrow passage between two banyan trees in the hope of attaining good fortune or fulfilling personal wishes. This predominantly mythological interpretation has confined scholarly discussions to the domains of folklore, tourism, and Javanese cosmology, leaving its potential relationship with the Sufi concept of sulūk largely unexplored. This study therefore aims to reinterpret Masangin as a symbolic process of spiritual transformation through the lens of Sufi metaphysics. Method: This study employed a qualitative research design using in-depth interviews, participant observation, and document analysis to collect data. The data were analyzed following Creswell’s qualitative analysis procedures, including data organization, coding, thematic categorization, interpretation, and the presentation of findings through analytical tables. Results: The findings reveal that the Masangin tradition embodies a coherent sequence of symbolic stages corresponding to the Sufi spiritual journey (sulūk). The blindfold symbolizes detachment from worldly perception (takhallī), walking in a straight direction represents steadfastness on the spiritual path (istiqāmah), passing between the two banyan trees signifies spiritual striving (mujāhadah), maintaining bodily balance reflects the purification of the soul (tazkiyah al-nafs), and successfully reaching the destination symbolizes spiritual proximity to God (qurb ilā Allāh). These interconnected symbols demonstrate that Masangin functions not merely as a cultural ritual but also as a symbolic representation of progressive spiritual formation. Conclusion: This study proposes the Sulūk Symbolism Framework, which repositions the Masangin tradition from a wish-fulfillment myth into a systematic model of Sufi spiritual education. The framework offers a new theoretical perspective for understanding Javanese cultural practices as vehicles for the internalization of Sufi values while enriching scholarly discussions on the intersection between local traditions, Islamic metaphysics, and symbolic spiritual pedagogy.